Computer, informatics, cybernetics and applications : Proceedings of the CICA 2011 - He, Xingui (Lecture Notes in Electrical Engineering, 2012)
Computer Informatics Cybernetics and Applications offers 91 papers chosen for publication from among 184 papers accepted for presentation to the International Conference on Computer, Informatics, Cybernetics and Applications 2011 (CICA 2011), held in Hangzhou, China, September 13-16, 2011. The CICA 2011 conference provided a forum for engineers and scientists in academia, industry, and government to address the most innovative research and development including technical challenges and social, legal, political, and economic issues, and to present and discuss their ideas, results, work in progress and experience on all aspects of Computer, Informatics, Cybernetics and Applications. Reflecting the broad scope of the conference, the contents are organized in these topical categories: Communication Technologies and Applications Intelligence and Biometrics Technologies Networks Systems and Web Technologies Data Modeling and Programming Languages Digital Image Processing Optimization and Scheduling Education and Informatics Fuzzy System and Control Forensics, Recognition Technologies and Applications Electronic Applications Graphics and Visualizing Green Computing Data Management and Database System E-commerce and E-government Social and Economical Systems Web Service and Data Mining  These papers provide novel ideas, new results, descriptions of work in progress and state-of-the-art techniques in the field. Moreover, they will serve to stimulate new research activities in the area of Computer, Informatics, Cybernetics and Applications.